Tornedalsk identitet : En studie om identiteter och deras påverkan på synen av den svenska staten - Karlsson, Ingrid (Fakulteten för samhälls- och livsvetenskaper, 2007)
ABSTRACT This C-essay in political science is written by Ingrid Karlsson, autumn 06. Advisers: Gregg Bucken-Knapp and Susan Marton. “ The identity of Tornedalen, a study about identities and its affect on the view of the Swedish state.” The purpose of this essay is to investigate the identification amongst the population in Tornedalen and if their identity affects the view of the Swedish state. I am going to look into how people from that region looks upon their identity. Do they consider themselves as Swedish, Tornedaling or Finnish? I have two research questions on this topic: 1) What does a person from Tornedalen consider their identity? 2) If the way the Swedish state treated Tornedalen, from around the middle of the nineteenth century to the middle of the twentieth century, has affected the way people from this region looks upon their own culture, and if the treatment has affected peoples view of the Swedish state. The methods I am using for this essay is case studies and to my help to collect data I am having a focus group in Pajala. My reason to use a focus group instead of surveys is because I find focus groups to be a much more interesting way of finding out what people really think. My conclusion on the question about identity is that the people in Tornedalen have different ideas on how they see themselves. Some consider themselves as both Tornedaling and Swedish, and others see themselves as Finnish and Swedish. One thing that I found out through the focus group is that a mutual thing amongst the participators is that they see themselves as Swedish. On my second question, my conclusion is that the way the Swedish state treated this region had a great impact on how they look upon themselves and their view of the Swedish state.